PET/CT in restaging, prognosis, and recurrence in patients with malignant melanoma - Kholoud H. El-Shourbagy; Emad M. Mashaly; Sameh A. Khodair; Mohamed M. Houseni; Rania S. Abou Khadrah (The Egyptian Journal of Radiology and Nuclear Medicine, 2020)
Abstract Background Cutaneous malignant melanoma (CMM) is a highly aggressive tumor with high tendency of return despite complete surgical removal. It has a high risk of dissemination to regional lymph nodes and visceral organs. The prognosis is highly dependent on lymph node involvement and distant metastases. Positron Emission Tomography with Computed Tomography (PET/CT) is a valuable non-invasive tool for the diagnosis and staging of patients with MM. The purpose of the present study was to evaluate the role of integrated (PET/CT) in staging, restaging, prognosis, and prediction of recurrence in patients with malignant melanoma. Results Fifty malignant melanoma patients with age ranged from 28 to74 years (mean age 55.94 + 13.40 years) were 28 males (mean age 56.71 + 12.82) and 22 females (mean age 54.95 + 14.34). All our patients were histopathologically proven to have malignant melanoma. Twenty-one patients came for initial staging by 18F-FDG PET/CT. Their findings were compared with the reference standards and showed the sensitivity of 93.33%, specificity of 60%, and accuracy of 85.71% for primary staging. 18F-FDG PET/CT scan in 11 clinical suspicion patients of relapse after treatment showed the sensitivity of 100%, specificity of 66.66%, positive predictive value of 88.88%; negative predictive value of 100%; and accuracy of 90.90%. FDG-PET/CT of whole body scan in 18 cases of stage IV melanoma showed sensitivity of 100%, specificity of 66.66%, and overall accuracy of 94.44% for detection of distant metastases. SUVmean and SUVmax in all studied groups were significantly higher in true positive more than true negative or false-positive patients diagnosed by PET/CT with high sensitivity (82.88–100%). Conclusion PET/CT imaging enhanced diagnostic performance in detection of the primary malignancy, in follow-up of high-risk patients and patients with suspected or known local or distant recurrence, and in restaging of patients with known distant metastatic disease to assess tumor response.